2015
DOI: 10.1016/j.breast.2015.09.007
|View full text |Cite
|
Sign up to set email alerts
|

The preoperative plasma fibrinogen level is an independent prognostic factor for overall survival of breast cancer patients who underwent surgical treatment

Abstract: Elevated preoperative plasma fibrinogen was independently associated with poor prognosis in breast cancer patients and may serve as a valuable parameter for risk assessment in breast cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 37 publications
4
52
3
Order By: Relevance
“…[6, 9, 10, 1214, 19] Tang et al [6] reported that increased EBV-DNA and fibrinogen levels alone and in combination are associated with reduced survival rates in stage I-IV NPC patients treated with either conventional radiotherapy, three-dimension conformal radiotherapy or IMRT. Our study reconfirmed that the gradual increases in FIB were associated with poorer survival outcomes in stage IVA/B diseases in the era of IMRT, but failed to confirm the value EBV-DNA load in this group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…[6, 9, 10, 1214, 19] Tang et al [6] reported that increased EBV-DNA and fibrinogen levels alone and in combination are associated with reduced survival rates in stage I-IV NPC patients treated with either conventional radiotherapy, three-dimension conformal radiotherapy or IMRT. Our study reconfirmed that the gradual increases in FIB were associated with poorer survival outcomes in stage IVA/B diseases in the era of IMRT, but failed to confirm the value EBV-DNA load in this group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have provided strong evidence that plasma fibrinogen is associated with tumor progression and poor prognosis in lung cancer, [4] breast cancer, [5] gastric cancer, [6] ovarian cancer, [7] oral and oropharyngeal cancer, [8] biliary tract cancer, [9] and penile cancer [10] patients. Fibrinogen is a 340-kDa glycoprotein that is synthesized in the liver and converted into fibrin by active thrombin.…”
Section: Introductionmentioning
confidence: 99%
“…The high fibrinogen level before operative was a risk factor for triple negative breast cancer and some other breast cancer subtypes. 6. Here, we concern about two routinely tested serums biochemical index alkaline phosphatase (ALP) and lactate dehydrogenase (LDH).…”
Section: Introductionmentioning
confidence: 99%